Novel Intranasal Drug Delivery: Geraniol Charged Polymeric Mixed Micelles for Targeting Cerebral Insult as a Result of Ischaemia/Reperfusion - Sara M. Soliman; Nermin M. Sheta; Bassant M. M. Ibrahim; Mohammad M. El-Shawwa; Shady M. Abd El-Halim (MDPI AG, 2020)
Brain damage caused by cerebral ischaemia/reperfusion (I/R) can lead to handicapping. So, the present study aims to evaluate the prophylactic and therapeutic effects of geraniol in the form of intranasal polymeric mixed micelle (PMM) on the central nervous system in cerebral ischaemia/reperfusion (I/R) injury. A 32 factorial design was used to prepare and optimize geraniol PMM to investigate polymer and stabilizer different concentrations on particle size (PS) and percent entrapment efficiency (%EE). F3 possessing the highest desirability value (0.96), with a PS value of 32.46  ±  0.64 nm, EE of 97.85  ±  1.90%, and release efficiency of 59.66  ±  0.64%, was selected for further pharmacological and histopathological studies. In the prophylactic study, animals were classified into a sham-operated group, a positive control group for which I/R was done without treatment, and treated groups that received vehicle (plain micelles), geraniol oil, and geraniol micelles intranasally before and after I/R. In the therapeutic study, treated rats received geraniol oil and micelles after I/R. Evaluation of the effect of geraniol on behavior was done by activity cage and rotarod and the analgesic effect tested by hot plate. Anti-inflammatory activity was assessed by measuring interleukin β6, cyclooxygenase-2, hydrogen peroxide, and inducible nitric oxide synthase. Histopathogical examination of cerebral cortices was also done to confirm the results of a biochemical assay. Geraniol nanostructured polymeric mixed micelles showed an enhanced neuro-protective effect compared to geraniol oil, confirming that PMM via intranasal route could be an efficient approach for delivering geraniol directly to the brain through crossing the blood−brain barrier.